Calcifying epithelial odontogenic tumor: a case series from South America - de Arruda, José Alcides Almeida; Ventura, José Victor Lemos; Barreto, Maria Eduarda Zeraik; Villarroel-Dorrego, Mariana; Peña-Vega, Claudia Patricia; Rodríguez-Mora, Juan Pablo; Rojas-Ponte, Alejandra; Cavalcante, Israel Leal; Pereira, José Ricardo Dias; Sampaio, Gerhilde Callou; Valle, Isabella Bittencourt do; Faccin, Kallana Mezzomo; et al. (Journal of Oral Diagnosis, 2025)
Objective: To describe a case series of calcifying epithelial odontogenic tumor (CEOT) from South America. Methods: This study analyzed cases from Brazil (n=7), Venezuela (n=4), and Colombia (n=1), providing their clinicopathologic, radiographic, and treatment characteristics. Results: The series comprised seven (58.3%) females and five (41.7%) males, with a mean age at diagnosis of 33.4 years (range: 19–61). Clinically, 66.7% of patients presented with swelling, and the duration of the lesions ranged from 24 to 120 months. The mandible was involved in 91.7% (n=11) of cases, predominantly in the posterior region (83.4%). Radiographically, 83.4% of lesions were expansive, 75% displayed mixed density, 58.4% were associated with an impacted tooth, and 50% showed root resorption. The median lesion size was 45 mm. Histopathologically, 10 (83.3%) cases were classified as “classic” CEOT, while two (16.7%) were identified as the clear-cell variant. Curettage was performed in 50% of cases and surgical removal (en bloc) in 33.3%. No recurrences were observed in nine (81.8%) cases over a median follow-up of 36 months. Conclusion: These findings align with existing literature, highlighting a predominance of young adult females who often present with asymptomatic swelling. The importance of vigilant long-term follow-up post-treatment is emphasized.